Individual characteristics, area social participation, and primary non-concordance with medication: a multilevel analysis - Eriksson Charli; Sundquist Jan; Lindström Martin; Johnell Kristina; Merlo Juan (BMC, 2006)
Abstract Background Non-concordance with medication remains a major public health problem that imposes a considerable financial burden on the health care system, and there is still a need for studies on correlates of non-concordance. Our first aim is to analyse whether any of the individual characteristics age, educational level, financial strain, self-rated health, social participation, and trust in the health care system are associated with primary non-concordance with medication. Our second aim is to investigate whether people living in the same area have similar probability of primary non-concordance with medication, that relates to area social participation. Methods We analysed cross sectional data from 9 070 women and 6 795 men aged 18 to 79 years, living in 78 areas in central Sweden, who participated in the Life & Health year 2000 survey, with multilevel logistic regression (individuals at the first level and areas at the second level). Results Younger age, financial strain, low self-rated health, and low trust in the health care system were associated with primary non-concordance with medication. However, area social participation was not related to primary non-concordance, and the variation in primary non-concordance between the areas was small. Conclusion Our results indicate that people in central Sweden with younger age, financial difficulties, low self-rated health, and low trust in the health care system may have a higher probability of primary non-concordance with medication. However, the area of residence - as defined by administrative boundaries - seems to play a minor role for primary non-concordance.